Exceeding the goal : adventures in strategy, information technology, computer software, technical services, and Goldratt's theory of constraints - Ricketts, John Arthur (Industrial Press, Inc., 2020)
Provides a broader understanding of strategy and information to the Theory of Constraints community while introducing TOC principles to the strategy and information communities. The author uses his own experiences in manufacturing, research, consulting, software, and strategy as the basis for the book.
Keywords: Production management.; elektronické knihy; electronic books